Oral delivery of double-stranded RNAs induces mortality in nymphs and adults of the Asian citrus psyllid, Diaphorina citri. - Diogo Manzano Galdeano; Michèle Claire Breton; João Roberto Spotti Lopes; Bryce W Falk; Marcos Antonio Machado (PLoS ONE, 2017)
The Asian citrus psyllid (ACP), Diaphorina citri Kuwayama, is one of the most important citrus pests. ACP is the vector of the phloem-limited bacteria Candidatus Liberibacter americanus and Candidatus Liberibacter asiaticus, the causal agents of the devastating citrus disease huanglongbing (HLB). The management of HLB is based on the use of healthy young plants, eradication of infected plants and chemical control of the vector. RNA interference (RNAi) has proven to be a promising tool to control pests and explore gene functions. Recently, studies have reported that target mRNA knockdown in many insects can be induced through feeding with double-stranded RNA (dsRNA). In the current study, we targeted the cathepsin D, chitin synthase and inhibitor of apoptosis genes of adult and nymph ACP by feeding artificial diets mixed with dsRNAs and Murraya paniculata leaves placed in dsRNAs solutions, respectively. Adult ACP mortality was positively correlated with the amount of dsRNA used. Both nymphs and adult ACP fed dsRNAs exhibited significantly increased mortality over time compared with that of the controls. Moreover, qRT-PCR analysis confirmed the dsRNA-mediated RNAi effects on target mRNAs. These results showed that RNAi can be a powerful tool for gene function studies in ACP and perhaps for HLB control.